Alteration of GABAergic neurotransmission in Huntington's disease. (21st February 2018) - Garret, Maurice; Du, Zhuowei; Chazalon, Marine; Cho, Yoon H.; Baufreton, Jérôme
Summary: Hereditary Huntington's disease (HD) is characterized by cell dysfunction and death in the brain, leading to progressive cognitive, psychiatric, and motor impairments. Despite molecular and cellular descriptions of the effects of the HD mutation, no effective pharmacological treatment is yet available. In addition to well‐established alterations of glutamatergic and dopaminergic neurotransmitter systems, it is becoming clear that the GABAergic systems are also impaired in HD. GABA is the major inhibitory neurotransmitter in the brain, and GABAergic neurotransmission has been postulated to be modified in many neurological and psychiatric diseases. In addition, GABAergic neurotransmission is the target of many drugs that are in wide clinical use. Here, we summarize data demonstrating the occurrence of alterations of GABAergic markers in the brain of HD carriers as well as in rodent models of the disease. In particular, we pinpoint HD‐related changes in the expression of GABAA receptors (GABAA Rs). On the basis that a novel GABA pharmacology of GABAA Rs established with more selective drugs is emerging, we argue that clinical treatments acting specifically on GABAergic neurotransmission may be an appropriate strategy for improving symptoms linked to the HD mutation.